Roma and Egyptians in Albania: From Social Exclusion to Social Inclusion - De Soto, Hermine; Beddies, Sabine; Gedeshi, Ilir (Washington, DC: World Bank, 2012)
This report provides key insights into the social exclusion processes that affect Roma and Egyptian communities in Albania - two of the most vulnerable minority communities in Albania. It offers advice on the design of concrete actions to facilitate the inclusion of Roma and Egyptian communities into Albanian society, and also includes feedback from the Roma and Egyptian communities on the study findings and recommendations.